2013
DOI: 10.1080/13218719.2013.808978
|View full text |Cite
|
Sign up to set email alerts
|

Civil Law and Neuroscience

Abstract: The relationship between the brain and human behaviour is receiving increasing attention in legal practice. Much has already been published about the role of neuroscience in criminal law, but surprisingly little is known about its role in civil law. In this contribution, the relevance of neuroscientific insights within the civil law context will be demonstrated on the basis of examples in international publications from both continental and Anglo-American jurisdictions. Furthermore, a number of cases will be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This paper is aimed at portraying a model of the relation between cognitive science (henceforth CS) and legal philosophy (henceforth LP), with a special emphasis placed on what will be called the “ tension problem. ” The interactions between CS and law have been the subject of intensive research over the last twenty years (recently in particular in the context of so‐called neurolaw : see, e.g., Busey and Loftus 2006; de Kogel, Schrama, and Smit 2014; Pardo and Patterson 2013; Shen 2016). The relation between scientific knowledge about cognition and law (legal knowledge) is typically analyzed in the context of “law in action,” i.e., the opportunities for practical application of advances in neuroscience in legal procedures.…”
Section: Introductionmentioning
confidence: 99%
“…This paper is aimed at portraying a model of the relation between cognitive science (henceforth CS) and legal philosophy (henceforth LP), with a special emphasis placed on what will be called the “ tension problem. ” The interactions between CS and law have been the subject of intensive research over the last twenty years (recently in particular in the context of so‐called neurolaw : see, e.g., Busey and Loftus 2006; de Kogel, Schrama, and Smit 2014; Pardo and Patterson 2013; Shen 2016). The relation between scientific knowledge about cognition and law (legal knowledge) is typically analyzed in the context of “law in action,” i.e., the opportunities for practical application of advances in neuroscience in legal procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The second paragraph of Article 137 of the Slovenian Obligations Code, for example, stipulates that minors aged seven and over but under fourteen shall not be liable for damage, unless it is shown that they were capable of accounting for their actions when the damage was inflicted. When applying this article, the courts could take advantage of the established neuroscientific discovery that individual brain regions do not develop at the same time (De Kogel et al, 2013).…”
Section: Magyar: the Use Of Neuroscientific Discoveries In Criminal And Civil Evidence Lawmentioning
confidence: 99%
“…Despite the defendant's objection that the plaintiff's capacity for reasoning could be ascertained only with a medical opinion that was contemporaneous with the time when the partnership was registred, the court followed his claim and annulled the partnership. 9 The court's decision was based on the clinical method, taking into account the expert opinion that was created exclusively and specifically for the case before the court (De Kogel et al, 2013).…”
Section: Magyar: the Use Of Neuroscientific Discoveries In Criminal And Civil Evidence Lawmentioning
confidence: 99%